Macroeconomic consequences of the real-financial nexus: Imbalances and spillovers between China and the U.S. - Ke Pang; Pierre L. Siklos (Bank of Finland, Institute for Economies in Transition (BOFIT), 2015)
​Relying on quarterly data since 1998 we estimate, for China and the U.S., small scale econometric models that economize on the number of variables employed and yet are rich enough to provide useful insights about spillover effects between the two countries under different maintained assumptions about the exogeneity of the macroeconomic relationship between them. We conclude that inflation in China responds to credit shocks. Indeed, the monetary transmission mechanism in China resembles that of the US even if the channels through which monetary policy affects their respective economies differ. We also find that the monetary policy stance of the PBOC was helpful in mitigating the impact of the global financial crisis of 2008-9. Finally, spillovers from the US to China are significant and originate from both through the real and financial sectors of the US economy. Publication
URN:NBN:fi:bof-201501301039
Keywords: E58; E52; C32; 330; spillovers; monetary policy in China; dynamic factor models; credit